The expression: 4x² + 38x + 70 ; is a polynomial expression.
__________________________________________________________
^ 3 sqrt 750 + ^ 3 sqrt 2058 - ^ 3 sqrt 48
Rewriting the expression we have
^ 3 sqrt (6 * x ^ 3) + ^ 3 sqrt (6 * y ^ 3) - ^ 3 sqrt (6 * z ^ 3)
That is, we have the following equations:
6 * x ^ 3 = 750
6 * y ^ 3 = 2058
6 * z ^ 3 = 48
Clearing x, y and z we have:
x = 5
y = 7
z = 2
Then, rewriting the expression
x (^ 3 sqrt (6)) + y (^ 3 sqrt (6)) - z (^ 3 sqrt (6))
Substituting the values
5 (^ 3 sqrt (6)) + 7 (^ 3 sqrt (6 *)) - 2 (^ 3 sqrt (6))
10 (^ 3 sqrt (6))
answer
the simple form of the expression is
D) 10 ^ 3 sqrt 6
Answer:
Step-by-step explanation:
4.
a)
P = 2width + 2length
8x = 2x + 2 length; 8x-2x = 2 length; 6x=2 length
length = 3x
b)
sides= 1/4 of 3x = 3x/4
perimeter of square = 4* side = 4*3x/4 = 3x
c)
x= 4
P rectangle =8x= 8*4= 32
P square = 3x = 3*4 = 12
32-12 = 20 cm greater is the P rectangle than P of square
d)
A rectangle = 2x*x = 2*4*4 = 32
A square =(3x/4)² = (3*4/4)² = 9
32-9 = 23 cm² greater is the A rectangle than A of square
5.
4Comic+1 Nonfiction
4comic = 8y so 1 comic = 2y
1 nonfiction = (3+7y)+ 2y
a)
1 nonfiction = 7y+2y+3 = 9y+3
b)
total= 8y+9y+3 = 17y+3
if y=4
total = 17*4 +3 = $71
Answer:
d
Step-by-step explanation:
d
8(number of soup) times 3 =x (number of vegetable cans)